KEMENANGAN CALON WALIKOTA (PETAHANA) DAN STATUS HUKUM TERDAKWA ISTRI DI PILKADA KOTA SALATIGA TAHUN 2017 - Fadillah, Azis Nur; Adnan, Muhammad; Harsasto, Priyatno (Journal of Politic and Government Studies, 2018)
The Election System of the Regional Head is directly more able toaccommodate the interests of the people. It can be argued that the elections are amomentum that is quite appropriate for the variants of voter preferences that arethe dominant factor in conducting their political actions or behavior. In SalatigaCity Election in 2017, Yulianto and Muh Haris were the winners with 50.52%votes. The couple Yulianto and Muh Haris were the couple after being SalatigaMayor in 2011-2016. Support for nominees dominated by winning two regionalhead elections, but on the other side of the 2017 elections of the mayor of theYuliyanto municipal mayor, Kirnaningsih Point was accused of being a corruptioncase of Salatiga South Road Road Corruption.The theories used in this study are voter behavior by using 3 approachesthat are sociological, psychological and rational approaches. Research methodused in this research is quantitative method. Quantitative approaches haveemphasized their analysis of numerical data processed by statistical methods.Based on the research conducted by the author, there are several factorsthat affect the victory of Yulianto and Muh Haris in the Salatiga City Election in2017. Firstly, because of the attraction of the candidate figure, Yulianto and MuhHaris figure who are experienced and prominent since known often visits ormeetings directly with the community. Second, the defendant's status of defendantstatus did not influence the voters in determining their choice because the votersconsidered it to be a personal affair of candidates and more to see Yulianto'sfigure as a mayor. Third, sociological factors, in which case religious factors playan important role in making voter decisions. Yulianto and Muh Haris are the pairsof candidates representing Muslim leaders.Keywords: Incumbent, Candidate, Local Election